2018
DOI: 10.1002/cbic.201800493
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Metalloporphyrin‐Catalyzed Selective Methionine Alkylation in the Lanthipeptide Nisin

Abstract: Bioorthogonal catalytic modification of ribosomally synthesized and post‐translationally modified peptides (RiPPs) is a promising approach to obtaining novel antimicrobial peptides with improved properties and/or activities. Here, we present the serendipitous discovery of a selective and rapid method for the alkylation of methionines in the lanthipeptide nisin. Using carbenes, formed from water‐soluble metalloporphyrins and diazoacetates, methionines are alkylated to obtain sulfonium ions. The formed sulfonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Moreover, nisin was C-terminally modi ed with propargylamine and subsequently uorescently labelled without affecting membrane insertion as well as antibacterial activity [20]. Recently, Maaskant ve Roelfes [21] showed that methionine in nisin A could be modi ed by using a selective metalloporphyrin-catalyzed alkylation reaction. Unfortunately, they did not determine antimicrobial properties of modi ed nisin A.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nisin was C-terminally modi ed with propargylamine and subsequently uorescently labelled without affecting membrane insertion as well as antibacterial activity [20]. Recently, Maaskant ve Roelfes [21] showed that methionine in nisin A could be modi ed by using a selective metalloporphyrin-catalyzed alkylation reaction. Unfortunately, they did not determine antimicrobial properties of modi ed nisin A.…”
Section: Introductionmentioning
confidence: 99%
“…These ncAAs can be coupled to diverse probes by standard bio-orthogonal chemical reactions, such as copper-catalyzed alkyne-azide cycloadditions (CuAAC or click-chemistry), olen metathesis, and metalloporphyrin-catalyzed alkylation. 516 Click-based examples in peptide chemistry include the coupling of peptides to polyethylene glycols to increase their solubility and half-life, to uorophores in order to monitor the distribution or mode of action of a compound, and to sugars or any other chemical moiety to alter the activity spectrum. 517 ncAAs have been incorporated into RiPPs through three main routes, (1) by chemical synthesis of the linear precursor peptide containing the ncAAs in the desired locations for further in vitro modication, (2) by supplementation-based incorporation or (3) by codon reprogramming.…”
Section: Engineering Ripps Containing Non-canonical Amino Acidsmentioning
confidence: 99%
“…thiopeptides, as well as metalloporphyrin-catalyzed alkylation of methionine in nisin (Maaskant and Roelfes, 2019) as attempts to obtaining novel AMPs with improved properties and/or activities. However, it is difficult to mimic PTM machinery chemically, whereas classical peptide synthetic protocols such as solid-phase peptide synthesis (SPPS) could not cover the chemical complexity of these natural products.…”
Section: Beyond Classical Protein Engineering: Expanding the Scope Ofmentioning
confidence: 99%
“…In nature, this is normally achieved by site-selective PTMs that create special non-canonical amino acid side chains such as dehydroalanine (Dha) and dehydrobutyrine (Dhb) in lantibiotics ( Figure 3 ). To directly mimic these and similar PTMs, chemists used, e.g., rhodium-catalyzed arylations ( Key and Miller, 2017 ), P450-catalyzed cyclopropanations ( Gober et al, 2017 ), and photocatalytic activation ( de Bruijn and Roelfes, 2018 ) in thiopeptides, as well as metalloporphyrin-catalyzed alkylation of methionine in nisin ( Maaskant and Roelfes, 2019 ) as attempts to obtaining novel AMPs with improved properties and/or activities. However, it is difficult to mimic PTM machinery chemically, whereas classical peptide synthetic protocols such as solid-phase peptide synthesis (SPPS) could not cover the chemical complexity of these natural products.…”
Section: The Feasibility Of Genetic Engineering To Produce More Potenmentioning
confidence: 99%